Nanocarbon and its composites : preparation, properties and applications - Khan, Anish; Jawaid, Mohammad; Inamuddin, 1980-; Asiri, Abdullah M. (Woodhead Publishing series in composites science and engineering., 2019)
Nanocarbon and Its Composites: Preparation, Properties and Applications provides a detailed and comprehensive review of all major innovations in the field of nanocarbons and their composites, including preparation, properties and applications. Coverage is broad and quite extensive, encouraging future research in carbon-based materials, which are in high demand due to the need to develop more sustainable, recyclable and eco-friendly methods for materials. Chapters are written by eminent scholars and leading experts from around the globe who discuss the properties and applications of carbon-based materials, such as nanotubes (buckytubes), fullerenes, cones, horns, rods, foams, nanodiamonds and carbon black, and much more. Chapters provide cutting-edge, up-to-date research findings on the use of carbon-based materials in different application fields and illustrate how to achieve significant enhancements in physical, chemical, mechanical and thermal properties. Demonstrates systematic approaches and investigations from design, synthesis, characterization and applications of nanocarbon based composites Aims to compile information on the various aspects of synthesis, properties and applications of nano-carbon based materialsPresents a useful reference and technical guide for university academics and postgraduate students (Masters and Ph. D.)